First ATG101-recruiting small molecule degrader for selective CDK9 degradation via autophagy–lysosome pathway - Ye Zhong; Jing Xu; Huiying Cao; Jie Gao; Shaoyue Ding; Zhaohui Ren; Huali Yang; Yili Sun; Maosheng Cheng; Jia Li; Yang Liu (Acta Pharmaceutica Sinica B)
Cyclin-dependent kinase 9 (CDK9) is a member of the transcription CDK subfamily and plays a role in transcriptional regulation. Selective CDK9 degraders possess potent clinical advantages over reversible CDK9 inhibitors. Herein, we report the first ATG101-recruiting selective CDK9 degrader, AZ-9, based on the hydrophobic tag kinesin degradation technology. AZ-9 showed significant degradation effects and selectivity toward other homologous cell cycle CDKs in vitro and in vivo, which could also affect downstream related phenotypes. Mechanism research revealed that AZ-9 recruits ATG101 to initiate the autophagy–lysosome pathway, and forms autophagosomes through the recruitment of LC3, which then fuses with lysosomes to degrade CDK9 and the partner protein Cyclin T1. These dates validated the existence of non-proteasomal degradation pathway of hydrophobic driven protein degradation strategy for the first time, which might provide research ideas for chemical induction intervention on other types of pathogenic proteins.